Apodemes associated with limbs support serial homology of claws and jaws in onychophora (velvet worms). (10th September 2013) - de, Ivo; Mayer, Georg
<x xml:space="preserve">Abstract</x> Cover illustration. Although the onychophoran jaw blades are believed to be derivatives of foot claws, serial homology of these structures has not been demonstrated. In this issue of the Journal of Morphology, Oliveira and Mayer (pp. 1180–1190) investigate the evolutionary origin of the onychophoran jaws by searching for morphological landmarks and comparing the internal and external anatomy of jaws and distal leg portions in representatives of Onychophora. The cover image shows a subset of confocal z‐series from the muscles associated with the onychophoran jaws and jaw apodemes.